MOTIVASI BELAJAR DITINJAU DARI DUKUNGAN KELUARGA DAN SCHOOL WELL-BEING (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2021)
The role of the family has the influence to overcome all obstacles both from internal and external students in realizing all the ideals and hopes. Family support can increase learning motivation, sense of security and attention of students who are still in school. The form of family expression through empathy and acceptance helps students with enthusiasm to manifest individual enthusiasm in the learning process. High learning motivation is also caused by school well-being which is used by school institutions to understand all the basic needs for students and hope that individuals feel satisfaction, well-being and comfort in school with all the processes so as to reduce low learning motivation, this makes students feel prosperous, happy, happy in studying at school. This study aims to determine the effect of family support and school well-being on learning motivation in students of SMP Negeri 1 Telukjambe Timur Karawang. The number of samples used was 205 students of SMP Negeri 1 grades 7 and 8 East Telukjambe using probability sampling method. Based on the multiple regression analysis test that there is an influence between family support and school well-being on the learning motivation of students of SMP Negeri 1 Telukjambe Timur Karawang grades 7 and 8 with a Sign value. 0.000